2011
DOI: 10.1016/j.cyto.2011.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Early inflammation in the absence of overt infection in preterm neonates exposed to intensive care

Abstract: Background-Systemic inflammation, typically attributed to sepsis, has been repeatedly linked to adverse long-term outcomes in infants born prematurely. However, it is unclear whether other factors can contribute to potentially harmful systemic inflammatory responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…High circulating levels of inflammatory cytokines have been observed in very preterm infants exposed to intensive care (11) and have been repeatedly linked to worse outcomes such as bronchopulmonary dysplasia (12), white matter injury, and neurodevelopmental impairments (16). These results have led to speculations that the innate immune system of these infants is hyper-rather than hypo-responsive during the neonatal period (17).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…High circulating levels of inflammatory cytokines have been observed in very preterm infants exposed to intensive care (11) and have been repeatedly linked to worse outcomes such as bronchopulmonary dysplasia (12), white matter injury, and neurodevelopmental impairments (16). These results have led to speculations that the innate immune system of these infants is hyper-rather than hypo-responsive during the neonatal period (17).…”
Section: Discussionmentioning
confidence: 94%
“…We and others have shown that TLR-induced cytokine immune reactivity are profoundly attenuated in cord blood of very preterm neonates and develops asynchronously over the last trimester of gestation (6)(7)(8)(9)(10). These infants also display sustainably high levels of systemic inflammation, indicating a potential immune dysregulation that has also been associated with worsened clinical outcomes (11). On the other hand, cord blood responses may not adequately reflect important developmental adaptation occurring during the first few weeks after birth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings have important clinical implications, since earlier studies have indicated that transient bacteremia commonly occurs in infants with sepsis [100,101]. Another study has demonstrated persistent sub-clinical inflammation in the absence of overt clinical signs of infection in these infants throughout the neonatal period, possibly due to an ongoing exposure to intensive care therapies [102]. In light of these findings, better strategies will be necessary to both limit the sustained exposure of premature infants to any potential triggers of inflammation or sources of transient bacteremia, and to prevent infections [103].…”
Section: Lessons From Neonatal Mouse Modelsmentioning
confidence: 89%
“…38,[41][42][43][44] In extreme preterm infants, high systemic inflammatory biomarkers are measured in the earliest hours after birth and for extended periods of time during the neonatal period, particularly in infants exposed to mechanical ventilation and supplemental O 2 . [45][46][47][48][49] Preterm infants also have a limited ability to counteract inflammatory and oxidative stress during the neonatal period. 50 Sustained oxidative stress and inflammation are key factors contributing to the development of BPD as well as other neonatal complications.…”
Section: Figurementioning
confidence: 99%